Sociodemographic determinants of prevalence and incidence of Helicobacter pylori infection in Portuguese adults - Bastos, J (2013)
Background: Understanding the determinants of Helicobacter pylori infection in adults is essential to predict the burden of H. pylori‐related diseases. We aimed to estimate the prevalence and incidence of H. pylori infection and to identify its major sociodemographic correlates in an urban population from the North of Portugal. Material and Methods: A representative sample of noninstitutionalized adult inhabitants of Porto (n = 2067) was evaluated by ELISA (IgG) and a subsample (n = 412) was tested by Western Blot to assess infection with CagA‐positive strains. Modified Poisson and Poisson regression models were used to estimate crude and sex‐, age‐, and education‐adjusted prevalence ratios (PR) and incidence rate ratios (RR), respectively. Results: The prevalence of H. pylori infection was 84.2% [95% confidence interval (95%CI): 82.4–86.1]. It increased across age‐groups in the more educated subjects, (18–30 years: 72.6%; ≥71 years: 88.1%; p for trend <0.001) and decreased with education in the younger (≤4 schooling years: 100.0%; ≥10 schooling years: 72.6%; p for trend <0.001). Living in a more deprived neighborhood was associated with a higher prevalence of infection, only in the younger (PR = 1.20, 95%CI: 1.03–1.38) and more educated participants (PR = 1.15, 95%CI: 1.03–1.29). Among the infected, the proportion with CagA‐positive strains was 61.7% (95%CI: 56.6–66.9). The incidence rate was 3.6/100 person‐years (median follow‐up: 3 years; 95%CI: 2.1–6.2), lower among the more educated (≥10 vs ≤9: RR = 0.25, 95%CI: 0.06–0.96). The seroreversion rate was 1.0/100 person‐years (95%CI: 0.6–1.7). Conclusions: The prevalence of infection among adults is still very high in Portugal, suggesting that stomach cancer rates will remain high over the next few decades.